CHANGES OF ACTIVITY INDEX AND TOTAL SEVERITY INDEX IN PATIENTS WITH SYSTEMIC SCLEROSIS AND INTERSTITIAL LUNG DISEASE OVER A 5-YEAR FOLLOW-UP PERIOD - O. B. Ovsyannikova; L. P. Ananyeva; V. N. Lesnyak; O. A. Koneva; M. N. Starovoitova; O. V. Desinova (Научно-практическая ревматология)
Systemic sclerosis (SS) is a systemic disease, the basis for which is microcirculatory disorders, inflammation, and generalized fibrosis. Interstitial lung disease (ILD) is one of the primary manifestations of SS. Assessment of SS activity and severity is hindered as it is very difficult to differentiate fibrous and inflammatory changes that are mostly interrelated and have a similar picture.Objective: to estimate activity index (AI) and total severity index (TSI) for the follow-up of SS patients with different variants of ILD. Subjects and methods. The investigation enrolled 77 patients with SS and ILD, who were followed up at the V.A. Nasonova Research Institute of Rheumatology; their mean age at inclusion was 46±13 years. All the patients underwent high-resolution computed tomography (HRCT) of the chest and determination of TSI and AI scores at baseline and after an average of 59±12 months. According to the time course of HRCT revealed pulmonary changes over a 5-year follow-up, the patients were divided into 3 groups: 1) patients with improvement (n=16); 2) those without changes (n=39); 3) those with deterioration (n=22). The disease was regarded as active with AI scores of ≥3.Results and discussion. The mean AI scores for the entire patient cohort were low and substantially unchanged during the follow-up period, amounting to 2.1±1.55 and 2.37±1.55 (p > 0.05) at the start and at the end of the investigation, respectively. Following 5 years, only Group 3 showed AI scores of > 3. At inclusion, the groups did not differ in AI scores; however, 5 years later AI became significantly higher in Group 3 than that in Groups 1 and 2 (p = 0.004 and p=0.03, respectively). During the follow-up, TSI remained substantially unchanged and averaged 6.5±2.5 and 6.9±2.3 at inclusion and at the end of the investigation, respectively. Moreover, TSI tended to decline in Groups 1 and 2; but it significantly increased in Group 3 (p = 0.006) and at the end of the investigation it was significantly higher than that in Group 1 (p = 0.002). There was a direct correlation between AI and TSI in the total cohort of patients both at baseline and 5 years later (R = 0.57 and R = 0.53; p < 0.05). Direct correlations were found between the indices within Groups 2 (R = 0.51 and R = 0.37) and 3 (R = 0.67 and R = 0.71) at baseline and at the end of the follow-up, respectively; p < 0.05).Conclusion. In our investigation, AI and TSI reflected the course of ILD in patients with SS. ILD progression, as evidenced by HRCT, was followed by a significant increase in AI and TSI scores; they directly correlated between. Thus, AI and TSI may be used for monitoring progression of the disease.